NECK ABSCESS CAUSED BY MORGANELLA MORGANII - Chang, Chee Yik; Rajappan, Mahaletchumi; Zaid, Masliza; Ong, Edmund LC (Journal of Ayub Medical College Abbottabad, 2021)
A 43-year-old housewife with no prior medical illness presented with progressive right neck swelling for 3 months' duration, associated with dysphagia and trismus. She reported no history of fever, hoarseness of voice, constitutional symptoms, or contact with pulmonary tuberculosis. Physical examination revealed a large right neck swelling that was tender and fluctuant. CT of the neck and thorax showed a collection within the right carotid space, measuring 1.0Ã—3.1Ã—5.3 cm with resultant anterior displacement of the right submandibular gland, right common carotid artery and internal jugular vein (Figure-1). There were also multiple enlarged and necrotic lymph nodes in the right cervical region. She subsequently underwent incision and drainage of the right neck abscess in which 20 cc of purulent material was drained. Cultures of the purulent material, as well as the intraoperative tissue, grew Morganella morganii, susceptible to cefepime and carbapenems. The histopathological examination findings of the sampled lymph node were negative for both tuberculosis and malignancies. The patient was treated with intravenous cefepime 2 g twice daily for a total of 14 days. The neck swelling reduced in size, and she made a full recovery.